Classification and Construction of (k,3)-Arcs on Projective Plane Over Galois Field GF(7) - Ahmad, Adil M.; Al-Mukhtar, Aamal SH.; Faiyadh, Mahmood S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The purpose of this work is to study the classification and construction of (k,3)-arcs in the projective plane PG(2,7). We found that there are two (5,3)-arcs, four (6,3)-arcs, six (7,3)arcs, six (8,3)-arcs, seven (9,3)-arcs, six (10,3)-arcs and six (11,3)-arcs.         All of these arcs are incomplete.         The number of distinct (12,3)-arcs are six, two of them are complete.         There are four distinct (13,3)-arcs, two of them are complete and one (14,3)-arc which is incomplete.         There exists one complete (15,3)-arc.